Characterization of unrelated clinical Legionella pneumophila isolates in Catalonia by monoclonal subgrouping and sequence-based typing. (July 2016) - Garcia-Nuñez, Marian; Quero, Sara; Pedro-Botet, Maria Lluisa; Barrabeig, Irene; Avarez, Josep; Campoy, Irene; Sala, Maria Rosa; Parraga-Niño, Noemí; Minguell, Sofia; Caylà, Joan; Mateu, Lourdes; Sabria, Miquel
Aim: To characterize the genetic diversity of unrelated Legionella pneumophila clinical isolates in Catalonia and compare with other European regions.Methods: 95 unrelated isolates were analyzed using monoclonal antibodies and sequence-based typing, 1989–2013.Results: The isolates showed a high diversity (IOD 0.964) with a predominance of some profiles (ST37-Phialdelphia, ST23-Philadelphia and ST1-OLDA). All regions had predominant sequence types (STs) that differed between regions, and only 3% of STs were shared between the three regions.Conclusion: L. pneumophila clinical isolates from Catalonia presented a high diversity and can be used in epidemiological surveillance studies. The heterogeneous predominance of STs between European regions suggested a relationship between geographical distribution and virulence of some STs.